Borrelia burgdorferi outer surface protein C (OspC) binds complement component C4b and confers bloodstream survival. (26th September 2017) - Caine, Jennifer A.; Lin, Yi‐Pin; Kessler, Julie R.; Sato, Hiromi; Leong, John M.; Coburn, Jenifer
Abstract: Borrelia burgdorferi (Bb) is the causative agent of Lyme disease in the United States, a disease that can result in carditis, and chronic and debilitating arthritis and/or neurologic symptoms if left untreated. Bb survives in the midgut of the Ixodes scapularis tick, or within tissues of immunocompetent hosts. In the early stages of infection, the bacteria are present in the bloodstream where they must resist clearance by the innate immune system of the host. We have found a novel role for outer surface protein C (OspC) from B. burgdorferi and B. garinii in interactions with the complement component C4b and bloodstream survival in vivo. Our data show that OspC inhibits the classical and lectin complement pathways and competes with complement protein C2 for C4b binding. Resistance to complement is important for maintenance of the lifecycle of Bb, enabling survival of the pathogen within the host as well as in the midgut of a feeding tick when ospC expression is induced.